ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DIBURSA EFEK INDONESIA - DEWI SARI WIJOYO; SISCA CYNTIA HARTONO (E-Jurnal Akuntansi TSM, 2021)
The purpose of this study is to find the effect of return on equity, firm size, leverage, tax, growth opportunity, current ratio, and lagged dividend to dividend policy. The research data were obtained from public companies annual reports which are listed on Indonesia Stock Exchange (IDX). This study used sample data of 33 manufacturing companies for period 2012 to 2014. The research method used analysis multiple regression. This research results that the variable return on equity, tax and lagged dividend shows a significant relationship with dividend payout ratio. It also funds that the other variables which is firm size, leverage, growth and current ratio shows no significant relationship with dividend payout ratio